2002
DOI: 10.1177/104538902761402503
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a Class of Real-Time Switched Piezoelectric Shunts

Abstract: Experimental and anecdotal evidences have shown that state-switched control strategies for piezoelectric actuators can be advantageous. However, most discussions of the stability of these systems has relied on heuristic, or physically motivated, arguments. In this paper, we show that recent open-circuit-short-circuit (OC-SC) state-switching control laws can be viewed as hybrid dynamical systems of Witsenhausen type. Within this framework, the closed-loop stability of OC/SC switching is rigorously established u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Since state switching has little effect on the power input to a system and all this input power must be dissipated by the system's dampers, maximizing the work extracted by the SSA's damper leads to reduced motion in the base to which the absorber is attached. Kurdila et al (2002) have researched the stability of state-switched systems. They showed that certain switching rules could induce instabilities in systems.…”
Section: Maximum Work Extraction Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since state switching has little effect on the power input to a system and all this input power must be dissipated by the system's dampers, maximizing the work extracted by the SSA's damper leads to reduced motion in the base to which the absorber is attached. Kurdila et al (2002) have researched the stability of state-switched systems. They showed that certain switching rules could induce instabilities in systems.…”
Section: Maximum Work Extraction Investigationmentioning
confidence: 99%
“…However, switching at maximum strain causes undesirable shocks in the response of the system (Larson and Rogers, 1994;Larson, 1996;Larson et al, 1998;Larson and Cunefare, 2004). State-switched systems are not, in general, stable (Kurdila et al, 2002). Certain switching laws can require an infinite energy input, which causes the system to become unstable (Kurdila et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general idea underlying most of the proposed control strategies is to use the maximum value of the control parameter when the resulting force is opposing to the motion of the vibrating mass, and the minimum value the other way around (Cunefare et al., 2000; Holdhusen and Cunefare, 2008; Jabbary and Bobrow, 2002; Shen et al., 2013; Mohammadi et al., 2015). For devices with variable stiffness, special attention must be paid in order to select the instants in which to perform the switch in order to ensure stability of the response (Kurdila et al., 2002). On the other hand, if the switch is performed on the damper coefficient, no stability problems arise, since this dissipative component is not capable of storing energy.…”
Section: Introductionmentioning
confidence: 99%
“…However, switching at maximum strain has the potential to cause undesirable mechanical transients (shocks or ringing) in the system (Larson and Rogers, 1994;Larson, 1996;Larson et al, 1998;Larson and Cunefare, 2004). Kurdila et al (2002) showed that a state-switched system with an external energy source could be switched in such a way that leads to instability.…”
Section: Introductionmentioning
confidence: 99%